2018
DOI: 10.1039/c8cc01177j
|View full text |Cite
|
Sign up to set email alerts
|

Assembly–disassembly switching of self-sorted nanotubules forming dynamic 2-D porous heterostructure

Abstract: We report the pH-driven formation of a dynamic 2-D porous heterostructure through assembly-disassembly switching of the stacked macrocycles of nanotubules and their subsequent spreading on the surfaces of a self-sorted sheet assembly in a hierarchical co-assembly. The 2-D ordered porous heterostructure is able to discriminate spherical C from flat coronene through shape selective adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…These results contrast with those previously observed for the neutral ligand L 1 , in which a strong gelation ability was found. Thus, it can be concluded that protonation of the pyridyl group of L 1 does not cause the disassembly of the fibers into the free monomers, as commonly observed for various pH‐responsive organogelators, but rather to a new molecular rearrangement leading to distinct aggregate morphology. No circular dichroism (CD) signals could be oberved upon cooling from 363 to 283 K ( c= 5×10 −4 m ; Figure S5, Supporting Information), indicating a non‐preferred (racemic mixture of P and M helices) organization of the achiral L 1 :TFA in MCH.…”
Section: Resultsmentioning
confidence: 99%
“…These results contrast with those previously observed for the neutral ligand L 1 , in which a strong gelation ability was found. Thus, it can be concluded that protonation of the pyridyl group of L 1 does not cause the disassembly of the fibers into the free monomers, as commonly observed for various pH‐responsive organogelators, but rather to a new molecular rearrangement leading to distinct aggregate morphology. No circular dichroism (CD) signals could be oberved upon cooling from 363 to 283 K ( c= 5×10 −4 m ; Figure S5, Supporting Information), indicating a non‐preferred (racemic mixture of P and M helices) organization of the achiral L 1 :TFA in MCH.…”
Section: Resultsmentioning
confidence: 99%
“…Amphiphile 1 was reported to self‐assembles into flat sheet structures surrounded by negatively‐charged carboxylates in neutral pH (Figure ) . The sheets are free standing in bulk solution with a thickness of 2.8 nm, demonstrating that the aromatic rods of 1 are packed in a monolayer arrangement in which the rods are aligned parallel to the sheet plane.…”
Section: Figurementioning
confidence: 99%
“…Amphiphile 1 was reported to self-assembles into flat sheet structures surroundedb yn egatively-chargedc arboxylates in neutral pH ( Figure 1). [29] The sheets are free standing in bulk solution with at hickness of 2.8 nm, demonstrating that the aromatic rods of 1 are packed in am onolayer arrangement in which the rods are aligned parallel to the sheet plane. Then, the aggregation behaviour of ac ationic distyrylanthracene (DSA) derivative 3 with AIE property [30] was investigated in presence of the self-assembled sheetso f1 in aqueous solution at pH 7.4.…”
mentioning
confidence: 96%
“…Among the nanostructures reported, ordered porous networks, which are considered as one of the most important structures in nanotechnology, have found their utility in catalysis, 31 enantiomer sieving, 31 molecular recognition, 31,32 surface adsorption, 32 membrane channels 33 and lithium storage 34 by rational molecular design. 31 Therefore, exploring ways of producing ordered porous networks and manipulating pore sizes to perform a certain function are of paramount signicance.…”
Section: Introductionmentioning
confidence: 99%
“…36 Another strategy is by molecular stacking, which makes use of molecules of rationally designed shapes and angles to form the desired porous network structure. 31,32 For instance, rigid hexagonal macrocycles and bent molecules have been used to form porous network through dimeric stacks, 31 or through electrostatic spreading of pre-assembled macrocycles. 32 There have also been reports where metal coordination plays a role to assist formation of monomeric pores before aggregation to form a porous network by molecular stacking.…”
Section: Introductionmentioning
confidence: 99%